Estudo comparativo da eficiência de diferentes processos oxidativos para o tratamento de águas residuais contendo pesticidas - Gromboni, Caio Fernando (2008)
Due to the vast amount of waste containing solutions of pesticides normally generated in cattle farms, in this study were evaluated different processes aiming its degradation. Initially were studied, two chamber photo-oxidative, which showed potential for the degradation of wastewater. Another alternative was investigate it was the coupling between microwave (MW) and ultraviolet (UV) radiation. To evaluate the efficiency of decomposition of the system were determinate the levels of initial carbon and after the treatments, using optical emission spectrometry with inductively coupled plasma. To identify the subproducts generated, chromatographic techniques were employed. In laboratory scale, the results indicated high efficiencies for degradation of wastewater, mainly for the tests performed with the photo-Fenton reaction, which had rates of decline exceeding 90%. It was noted that the decomposition of the wastewater of Colosso® pesticide is simpler when compared to the treatment of Supocade® pesticide. After the assessments in scale laboratory was built a prototype that employs Fenton reaction and agitation to be employed directly in the field. This prototype was tested and showed efficiencies of degradation of 60% for Supocade®, while for the Colosso® about 95% of the original carbon content has been removed from the solution, showing that the behaviour of reactions depends of active principle that compound the commercial product.